Investigation of the October effect in very low-frequency (VLF) signals - M. Hansen; D. Banyś; M. Clilverd; D. Wenzel; T. Raita; M. M. Hoque (Annales Geophysicae)
Subionospheric very low-frequency (VLF) radio signals are reflected by free electrons in the ionospheric D-region at about 60–90 km altitude and can propagate over long distances, which makes them useful for monitoring the state of the D-region or perturbations due to solar flares. At the D-region height, the ionosphere is mainly ionized by solar Lyman-α radiation. The reflection characteristics of VLF signals depend on the state and dynamics of the D-region, which is highly influenced by Lyman-α radiation. Although the amplitude of the received terrestrial VLF signal changes as a function of solar zenith angle over the course of the year, the VLF amplitude shows a distinctive sharp decrease around October, which is hence called the “October effect”. This study investigates the occurrence of the October effect and its dependencies on latitude and longitude. We developed a method to detect the occurrence of the October effect in the long-term VLF data and derive key parameters characterizing (start and end date, intensity) the sudden decrease in the signal amplitude. This investigation using a network of VLF stations distributed over low-, middle-, and high-latitude regions shows that the occurrence of the October effect has a clear latitudinal dependency, occurring earlier in high-latitude regions than at midlatitudes. No low-latitude signature is found.